Penyelesaian Sengketa Perlindungan Data Pribadi Melalui Arbitrase di Era Society 5.0 - Claudia, Zulian (Jurnal Supremasi, 2024)
The advancement of technology in the Society 5.0 era has led to the negative impact of personal data breaches, causing significant losses in the business sector due to the critical role of personal data. However, research on dispute resolution methods for personal data protection remains limited. This study aims to analyze the legal protection of consumer personal data and the methods of dispute resolution available in cases of personal data protection disputes. Using a normative legal research method, the study finds that the government has enacted the Personal Data Protection Law as a form of preventive and repressive protection. Additionally, the law provides the parties with the option to resolve disputes through arbitration. These findings demonstrate legal certainty in personal data protection in Indonesia, with implications for the business sector in utilizing more flexible dispute resolution mechanisms.